The whisper - Starmer, Aaron, 1976- (Starman, Aaron, 1976- Riverman trilogy, 2016)
Twelve-year-old Alistair continues his quest to find his missing friend, Fiona, in Aquavania, a world where wishes can nearly come true, but he learns that the Whisper, once a boy named Charlie from his own world, has plans for Alistair and has used Fiona to try to get to him.